Integrated catchment management : the Mooi River (Northwest Province, South Africa) as a case study - Walt, J. van der; Nell, B.; Winde, F. (Cuadernos de Investigación Geográfica, 2013)
The city of Potchefstroom is situated at the lower end of the Mooi River catchment. Since 1842 the Mooi River has been the sole water supply of Potchefstroom, which currently has about 210 000 residents. The Mooi River is fed mainly by dolomitic eyes and springs. Since the 1930’s, large-scale gold mining commenced to work the ore, which occur in the Witwatersrand sedimentary layer underlying the dolomites. To reduce the danger of flooding, some dolomitic compartments were dewatered by the gold mines, sometimes resulting in catastrophic environmental impacts. Furthermore, slimes dams1 were constructed on dolomitic areas resulting in the seepage of large volumes of polluted water into the underlying aquifer. The indiscriminate mining practices, as well as the rapid development of informal and formal settlements, some diamond mining enterprises as well as agriculture in the central and upper reaches of the catchment, resulted in a steady increase in salt loads in the water of the Mooi River, as well as the deposition of high concentrations of trace metals, especially uranium, which is associated with the gold bearing ore. Recently, it was announced that some mines in the Mooi River Catchment have reached the end of their productive lives, and that projects to re-water the dolomitic compartments were underway. This paper explores the possible environmental impacts associated with re-watering the dolomitic compartments, and indicates how a lack of integrated catchment planning and management are currently exacerbating the already manifested environmental impacts. Finally, an integrated approach to the rehabilitation and restoration of the catchment to a sustainable water resource is suggested.